Toxicokinetics and correlation of carbamazepine salivary and serum concentrations in acute poisonings - Đorđević Snežana; Kilibarda Vesna; Vučinić Slavica; Stojanović Tomislav; Antonijević Biljana (Vojnosanitetski Pregled)
Background/Aim. Saliva is a body fluid which, like serum, can be used for determination of concentrations of certain drugs, both in pharmacotherapy as well as in acute poisonings. The aim of this study was to determine carbamazepine concentrations in both saliva and serum in acute poisoning in order to show if there is a correlation between the obtained values, as well as to monitor toxicokinetics of carbamazepine in body fluides. Methods. Saliva and serum samples were obtained from 26 patients treated with carbamazepine and 20 patients acutely poisoned by the drug immediately after their admission in the Emergency Toxicology Unit. Determination of salivary and serum carbamazepine concentrations was performed by the validated high pressure liquid chromatographyultraviolet (HPLC-UV) method. Results. A significant correlation of salivary and serum carbamazepine concentrations in both therapeutic application and acute poisoning (r = 0.9481 and 0.9117, respectively) was confirmed. In acute poisonings the mean ratio between salivary and serum concentrations of carbamazepine (0.43) was similar to the mean ratio after its administration in therapeutic doses (0.39), but there were high inter-individual variations in carbamazepine concentrations in the acutely poisoned patients, as a consequence of different ingested doses of the drug. In acute poisoning the halftime of carbamazepine in saliva and serum was 12.57 h and 6.76 h, respectively. Conclusion. Our results suggest a possible use of saliva as an alternative biological material for determination of carbamazepine concentrations in therapeutic application and acute poisoning as well, and a possible extrapolation of the results obtained in saliva to serum concentrations of carbamazepine.